Empowering Youth Health Cadres as an Effort to Prevent Diabetes Mellitus among Adolescents in Banyumanik Village, Semarang City - Golo, Zefan Adiputra; Masrochah, Siti; Fahyudi, Asharul (Jurusan Keperawatan Politeknik Kesehatan Kementerian Kesehatan Palu, 2025)
The incidence of Diabetes Mellitus (DM) among adolescents in Semarang City increased from 242 cases in 2021 to 344 in 2022, highlighting a pressing need for effective preventive interventions. Peer education through Youth Health Cadres (KKR) is a promising strategy to address this issue. This community service program aimed to evaluate the impact of an educational intervention on DM-related knowledge among prospective KKRs at SMPN 12 Banyumanik. The program involved 20 students and was conducted through a single session comprising a pre-test, an interactive educational module on DM etiology and prevention, practical training, and a post-test. Knowledge was measured using a validated 20-item questionnaire. The results demonstrated the proportion of students achieving a 'good' knowledge level increased from 15% to 85%. In conclusion, the targeted educational intervention successfully enhanced the knowledge of Youth Health Cadres. This empowerment provides a critical foundation for their role as agents of change in disseminating DM prevention information within their school environment, contributing to broader public health efforts against the disease.